2021
DOI: 10.1002/joc.7336
|View full text |Cite
|
Sign up to set email alerts
|

A reconstruction of June–July temperature since AD 1383 for Western Sichuan Plateau, China using tree‐ring width

Abstract: Global warming has a significant impact on the ecosystem of the high‐altitude areas of the Tibetan Plateau, such as land degradation and the rapid retreat of glaciers. It is important to understand the effects of global warming occurring over hundreds or thousands of years. However, the long‐term reconstruction of temperature is still lacking for the region of Western Sichuan Plateau (WSP). In this study, we reconstructed summer (June–July) temperatures back to 1383 for the WSP region based on a significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Peak streamflow in the UYR occurs during the summer season (Figure S1 in Supporting Information ). Previous study has shown that this region is dominantly influenced by ISM in boreal summer (Y. Zhang, Fang, et al., 2021; Y. Zhang, Li, et al., 2021). We also used the monthly gridded (2.5° × 2.5°) pressure, wind, and specific humidity (300500 hPa isobar data) data from the NCEP/NCAR reanalysis data set (Kalnay et al., 1996) to analyze the direction and distribution total water vapor flux over the study region and the surroundings.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Peak streamflow in the UYR occurs during the summer season (Figure S1 in Supporting Information ). Previous study has shown that this region is dominantly influenced by ISM in boreal summer (Y. Zhang, Fang, et al., 2021; Y. Zhang, Li, et al., 2021). We also used the monthly gridded (2.5° × 2.5°) pressure, wind, and specific humidity (300500 hPa isobar data) data from the NCEP/NCAR reanalysis data set (Kalnay et al., 1996) to analyze the direction and distribution total water vapor flux over the study region and the surroundings.…”
Section: Methodsmentioning
confidence: 94%
“…Therefore, we decided to apply isotope analyses to the trees cross‐dated by Y. Zhang, Li, et al. (2021), to investigate regional hydrological changes over the past centuries.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations